Quantitative PCR in epidemiology for early detection of visceral leishmaniasis cases in India. - Medhavi Sudarshan; Toolika Singh; Abhishek Kumar Singh; Ankita Chourasia; Bhawana Singh; Mary E Wilson; Jaya Chakravarty; Shyam Sundar (Public Library of Science (PLoS), 2014)
Studies employing serological, DTH or conventional PCR techniques suggest a vast proportion of Leishmania infected individuals living in regions endemic for Visceral Leishmaniasis (VL) remain asymptomatic. This study was designed to assess whether quantitative PCR (qPCR) can be used for detection of asymptomatic or early Leishmania donovani infection and as a predictor of progression to symptomatic disease.The study included 1469 healthy individuals living in endemic region (EHC) including both serology-positive and -negative subjects. TaqMan based qPCR assay was done on peripheral blood of each subject using kDNA specific primers and probes.A large proportion of EHC 511/1469 (34.78%) showed qPCR positivity and 56 (3.81% of 1469 subjects) had more than 1 calculated parasite genome/ml of blood. However, the number of individuals with parasite load above 5 genomes/ml was only 20 (1.36% of 1469). There was poor agreement between serological testing and qPCR (k = 0.1303), and 42.89% and 31.83% EHC were qPCR positive in seropositive and seronegative groups, respectively. Ten subjects had developed to symptomatic VL after 12 month of their follow up examination, of which eight were initially positive according to qPCR and among these, five had high parasite load.Thus, qPCR can help us to detect significant early parasitaemia, thereby assisting us in recognition of potential progressors to clinical disease. This test could facilitate early intervention, decreased morbidity and mortality, and possibly interruption of disease transmission.